Human-Oriented Approach in Forming of Key Competences of Civil Servants in the Conditions of Digital Transformation of the Economy - E. V. Vasilieva; V. N. Pulyaeva; V. A. Yudina (Управленческие науки)
The article is devoted to the issues of applying a human-focused approach in determining the competencies of civil servants and the directions of their qualifications development. The aim of the study is to develop a model of key competencies of state civil servants taking into account the requirements of official regulations, qualification requirements for professional knowledge and skills of civil servants, as reflected in regulatory and legal documents, as well as trends in a competence-based focus approach to development of potential of employees. There have been given the results of an expert survey conducted in 2018 among organizations of the public civil service of three constituent entities of the Russian Federation. The analysis showed that despite the transition of the civil service to the digital technologies and services, there had been paid not much attention to change the behavioral attitudes of personnel and their readiness for innovations. So, skills in using methods of project management, development of creative capabilities, empathy, and mentoring are not highly appreciated. As a rule, during choosing areas of advanced training, they prefer professional skills training programs, ignoring other formats aimed at development of the important soft skills in the digital economy. The use of a competence-based approach to the formation of a competencies model, methods of the analysis and in the synthesis of quantitative and qualitative parameters of the existing career management system of public civil servants allowed to substantiate the basic principles of introducing a human-oriented approach to the personnel work of state bodies. The authors proposed a model of key competencies for various groups of civil service positions. The main conclusions are formulated on the need to use analytical tools to monitor the current level of public civil service competencies development, as well as to develop recommendations about modeling in further professional and career growth. There has been proposed a classification of the “soft” skills and development instruments needed for the improvement of the professional activity of civil servants in a digitalization of the economy. The importance of the human-oriented approach in the competency model is caused by need of the work transformation of the public civil service under the conditions of the digital economy.